Determinants of the competitiveness of the regions of Eastern Poland - Jabłońska-Karczmarczyk, Katarzyna (Wyznaczniki konkurencyjności regionów wschodniej Polski, 2019)
The aim of the study is to draw attention to the current processes of adapting regions to the competitive situation. This is related to the globalization process and the disappearance of geographical and economic barriers. As a result, regions must actively monitor the market and respond to changes. The study presents the concept of region’s competitiveness, and an analysis of competitive ability factors. The rest of the article is an analysis of the conditions of competitiveness of Eastern Poland voivodeships using the multidimensional comparative analysis method
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 49-60